Comparison of Activation Methods for Coal Ash as an Adsorbent in the Removal of Lead (Pb²⁺) from Aqueous Solution - Budi Setya Wardhana; Farrah Fadhillah Hanum; Zahrul Mufrodi; Annisa Vada Febriani; Siti Salamah (Jurnal Kimia Sains dan Aplikasi, 2025)
Coal ash, also known as fly ash and bottom ash (FABA), is a byproduct of coal combustion that can be utilized as an adsorbent for removing lead (Pb2+) ions from wastewater. While previous studies have explored both unactivated and activated forms of FABA, few have directly compared their adsorption performance under identical operating conditions. This study investigates the characteristics of FABA before and after activation and evaluates its effectiveness in Pb2+ ion removal. Characterization was performed using X-ray fluorescence (XRF) for chemical composition and Brunauer-Emmett-Teller (BET) analysis for surface area and pore structure. XRF results showed that fly ash (FA) and bottom ash (BA) are dominated by Fe2O3, SiO2, and Al2O3, which contribute to the adsorption capacity. BET analysis revealed that FA has a higher specific surface area (6.377 m2/g) compared to BA (0.848 m2/g), indicating greater potential for adsorption. The adsorption performance was evaluated using Atomic Absorption Spectroscopy (AAS) after 60 minutes of contact time at an initial Pb2+ concentration of 100 ppm. Both FA and BA exhibited high Pb2+ removal efficiencies, reaching up to 100% under optimal conditions. Physical activation and chemical activation using neutral (H2O) and alkaline (NaOH and KOH) agents enhanced adsorption efficiency (98–100%), whereas activation with acidic agents (HCl and H2SO4) reduced it to 87–97%. These results demonstrate that FABA, particularly FA, has strong potential as an efficient and environmentally friendly adsorbent for heavy metal removal. The findings also suggest that water activation offers a simple and sustainable approach for large-scale wastewater treatment applications.